Research papers Microsecond hydrodynamic interactions in dense colloidal dispersions probed at the European XFEL. (2021) - Dallari, Francesco; Jain, Avni; Sikorski, Marcin; Mo¨ller, Johannes; Bean, Richard; Boesenberg, Ulrike; Frenzel, Lara; Goy, Claudia; Hallmann, Jo¨rg; Kim, Yoonhee; Lokteva, Irina; Markmann, Verena; et al.
No abstract available